Revision of a conchostracan form from the La Amarga Formation (Lower Cretaceous), Neuquén basin, Argentina - Gallego, Oscar Florencio (2004)
The Cretaceous conchostracan faunas from southern South America are poorly known, only five species were described from Argentina and Uruguay. In contrast, more than twenty seven species were reported from Brazil since the end of the 19th century. In this paper, Euestheria sp. A from the La Amarga Formation (Lower Early Cretaceous – Late Hauterivian to Barremian) in Neuquén Basin is re-studied and assigned to the genus Pseudestherites Chen. This finding found represents the sixth record of the genus in the world and the firstsecond outside China. This study increases the Cretaceous conchostracans knowledge from southern South America and brings more evidence about the close relationship among the ssouth american, african and asiatic conchostracan faunas.